2006
DOI: 10.1007/s10311-006-0040-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA adducts in fish following an oil spill exposure

Abstract: On 12 December 1999, one third of the load of the Erika tanker, amounting to about 10,000 t crude oil flowed into sea waters close to the French Atlantic Coast. This oil contained polycyclic aromatic compounds (PAC) that are known to be genotoxic. Genotoxic effects induce DNA adducts formation, which can thus be used as pollution biomarkers. Here, we assessed the genotoxic impact of the "Erika" oil spill by DNA adducts detection in the liver of immature fishes (Solea solea) from four locations of the French Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 37 publications
4
11
0
Order By: Relevance
“…Incubation of HePG2 cells lead to the formation of DNA adducts with similar patterns to the ones observed in the monitoring study using fish (Solea solea). These data indicates that human hepatocytes biotransform Erika fuel into genotoxic metabolites similarly to hepatic cells of fish and confirmed that the adducts observed in the monitoring study were related to the contamination of the sediment by the oil spill [173]. It has been shown that DNA adducts persisted in vertebrates species due to the low efficiency of repair systems, representing a parameter for long term exposure [174].…”
Section: Dna Adducts From Polycyclic Aromatic Hydrocarbonssupporting
confidence: 82%
See 1 more Smart Citation
“…Incubation of HePG2 cells lead to the formation of DNA adducts with similar patterns to the ones observed in the monitoring study using fish (Solea solea). These data indicates that human hepatocytes biotransform Erika fuel into genotoxic metabolites similarly to hepatic cells of fish and confirmed that the adducts observed in the monitoring study were related to the contamination of the sediment by the oil spill [173]. It has been shown that DNA adducts persisted in vertebrates species due to the low efficiency of repair systems, representing a parameter for long term exposure [174].…”
Section: Dna Adducts From Polycyclic Aromatic Hydrocarbonssupporting
confidence: 82%
“…Briefly, the assay involves DNA purification, digestion to normal and adduct-modified 3'-mononucleotides, removal of normal nucleotides (via enzymatic digestion, solvent extraction or chromatographic methods), 32 P-postlabelling at the 5' position of adducted nucleotides followed by chromatographic separation, detection and quantification (via autoradiography, scintillation counting or phosphor screen imaging analysis) [182]. Following this assay, PAHs cause the appearance of the diagonal radioactive zone (DRZ) (Figure 10) [173,178,183,184]. MS/MS analysis has recently emerged as a powerful tool in the detection and structure elucidation of DNA adducts as well as for their quantification at very low concentrations (as often present in biological samples).…”
Section: Dna Adducts From Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Noticeably, several of the estrogen-repressed miRNAs (miR-26, miR-107, miR-126 and miR-145) were also reduced by the physiological estrogen levels of vitellogenic females [ 8 ]. Thus, it can be assumed that estrogen-miRNA adducts could also affect fish reproduction and other estrogen-regulated biological processes [ 42 ], and could be used as bioindicators of xenoestrogens that pollute our environment [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that PAH metabolites and reactive oxygen species may be responsible for the DNA damage recorded 317 in this study (Regoli et al 2002;Fallahtafti et al 2012). We could expect MN, mutations and tumors induction at 318 later developmental stages as reported after fish exposure to Erika oil, Statfjord oil, or organic extract from the 319 Seine river sediment (Amat et al 2006; Baršienė et al 2006;Cachot et al 2007). However, aromatic extracts 320 may also contain traces of other chemicals which can also be toxic to fish in particular saturated hydrocarbons or 321 mono-aromatic compounds (González-Doncel et al 2008).…”
mentioning
confidence: 73%